Offensive realism, differentiation theory, and the war in Ukraine (2019)
In this article, I shall demonstrate that several of the arguments made in favour of an offensive realist explanation of Russian actions in Ukraine as part of a power balancing process are inconsistent both with available empirical knowledge of the conflict in Ukraine and with the structural logic postulated by offensive realist theory itself. Rather than a conflict about power in a material sense, I will argue that the war in Ukraine is better understood as a conflict about the incompatibility of the Russian state structure to cope with the imperatives of functional differentiation as understood by theories of world society. © 2018, Macmillan Publishers Ltd., part of Springer Nature.